Police Professionalism: Another Look at the Issues - Walker, Samuel (1976)
The concept of professionalism is frequently used as a frame of reference for evaluating the organizational status of the American police. Observers generally conclude that the police lack most of the essential features of professional status. This paper questions the utility of using such a standard for evaluating the police. The professions of medicine, law and education are themselves in a state of flux. In particular, the crucial concept of professional autonomy appears increasingly incompatible with the goal of public accountability. Rather than expect the police to strive toward the traditional forms of professionalism, we should think in terms of creating appropriate mechanisms for ensuring public accountability for all service occupations